Durability of GFRP connectors under sustained compression load for use in sandwich walls - Stefan Carstens; Matthias Pahn (Acta Polytechnica CTU Proceedings)
Precast concrete sandwich panels are used to fulfil the rising thermal requirements. The sandwich walls consist of three layers, a facing, a thermal insulation layer, and a load bearing layer. The two outer layers are coupled by connectors made of glass-fibre reinforced polymer. A lack of knowledge about load-bearing behaviour prevents the removal of sustained compressive loads. In the context of this article, tests under sustained compressive load are presented. To represent closely the in service-conditions of sandwich walls, the examined connectors were subjected to a saturated alkaline concrete environment as well as to a specified stress level till failure occurs. Thus, the experimental setup combines alkaline resistance and creep rupture tests into one comprehensive testing. By using temperature effects as an accelerating factor, reasonable test durations were enabled. The obtained time to failure line was determined to extrapolate the characteristic values of the long-term strength for a service life up to 50 years. The test results are compared and evaluated with existing test results under a sustained tensile load.